2000
DOI: 10.1128/jb.182.14.4005-4011.2000
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Mutational Analyses of theStreptomyces lividans recXGene and Its Interference with RecA Activity

Abstract: The role of the 20,922-Da RecX protein and its interference with RecA activity were analyzed in Streptomyces lividans. The recX gene is located 220 bp downstream of recA. Transcriptional analysis by reverse transcriptase PCR demonstrated that recX and recA constitute an operon. While recA was transcribed at a basal level even under noninducing conditions, a recA-recX cotranscript was only detectable after induction of recA following DNA damage. The recA-recX cotranscript was less abundant than the recA transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
76
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(89 citation statements)
references
References 38 publications
13
76
0
Order By: Relevance
“…Work in Pseudomonas aeruginosa, Mycobacterium smegmatis and Streptomyces lividans has demonstrated that overexpression of recA from a plasmid construct is deleterious or lethal in the absence of recX (Papavinasasundaram et al, 1997 ;Sano, 1993 ;Vierling et al, 2000), leading to the hypothesis that RecX acts by downregulating expression of recA or activity of the RecA protein. However, this hypothesis has not been rigorously tested, and a recX mutation of S. lividans does not affect any RecA-mediated processes or RecA levels (Vierling et al, 2000). Gc also contains a recX homologue ; however, it is not located downstream of recA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Work in Pseudomonas aeruginosa, Mycobacterium smegmatis and Streptomyces lividans has demonstrated that overexpression of recA from a plasmid construct is deleterious or lethal in the absence of recX (Papavinasasundaram et al, 1997 ;Sano, 1993 ;Vierling et al, 2000), leading to the hypothesis that RecX acts by downregulating expression of recA or activity of the RecA protein. However, this hypothesis has not been rigorously tested, and a recX mutation of S. lividans does not affect any RecA-mediated processes or RecA levels (Vierling et al, 2000). Gc also contains a recX homologue ; however, it is not located downstream of recA.…”
Section: Discussionmentioning
confidence: 99%
“…In mycobacteria and Streptomyces lividans the genes are cotranscribed (Papavinasasundaram et al, 1997 ;Vierling et al, 2000). Further work has led to the hypothesis that RecX acts by downregulating RecA activity (Sano, 1993 ;Papavinasasundaram et al, 1998 ;Vierling et al, 2000), though this hypothesis has not been directly tested, and a recX mutation in S. lividans does not affect any RecA-mediated processes or RecA expression levels. E. coli contains a RecX homologue located downstream of recA, designated oraA (Zaitsev et al, 1994).…”
Section: Abbreviation : Gc Neisseria Gonorrhoeaementioning
confidence: 99%
See 1 more Smart Citation
“…This argues against a direct role of recX in pheN duplication-related phenotypic switching from 1116S to 1116R forms in P. tolaasii. Although the precise role of recX in recA-mediated recombination is still under investigation, the ability of recX to reduce the toxicity of recA overexpression has been demonstrated in P. aeruginosa (18), Streptococcus lividans (20), and Mycobacterium smegmatis (16).…”
mentioning
confidence: 99%
“…The genetic instability of S. lividans strains was measured as the ratio of chloramphenicol-sensitive colonies, as described by Vierling et al (36).…”
mentioning
confidence: 99%